Pengaruh Kecepatan Pengiriman dan Price Discount terhadap Customer Satisfaction pada Pengguna GoFood - Putra, Suharto Balau; Harris, Allan (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2024)
The Effect of Delivery Speed ​​and Price Discount on Customer Satisfaction of GoFood Users in Indonesia. Customer satisfaction is the end result of a buying and selling transaction. Where if the customer's feelings are satisfied, it means that the performance produced by a product is successful. This type of research is quantitative causal, with primary data as the main data source with a sample of 121 respondents then processed using the data obtained from the questionnaire and processed with SPSS as an analysis tool from the multiple regression model. The results of this study, delivery speed has a positive effect on customer satisfaction, as well as the price discount variable has a positive effect on customer satisfaction. The results of the simultaneous test state that delivery speed and price discount simultaneously have a positive effect on customer satisfaction